Modern Stereoselective Synthesis of Chiral Sulfinyl Compounds - Wojaczyńska, Elżbieta (Chem Rev, 2020)
[Image: see text] Chiral sulfinyl compounds, sulfoxides, sulfoximines, sulfinamides, and other derivatives, play an important role in asymmetric synthesis as versatile auxiliaries, ligands, and catalysts. They are also recognized as pharmacophores found in already marketed and well-sold drugs (e.g., esomeprazole) and used in drug design. This review is devoted to the modern methods of preparation of sulfinyl derivatives in enantiopure or enantiomerically enriched form. Selected new approaches leading to racemic products for which the asymmetric variant can be developed in the future are mentioned as well.